The effect of age on outcome after intra-arterial treatment in acute ischemic stroke: a MR CLEAN pretrial study. Issue 1 (December 2016) - Beumer, Debbie; Rozeman, Anouk; Lycklama à Nijeholt, Geert; Brouwer, Patrick; Jenniskens, Sjoerd; Algra, Ale; Boiten, Jelis; Schonewille, Wouter; van Oostenbrugge, Robert; Dippel, Diederik; van Zwam, Wim
Abstract Background In recent randomized controlled trials (RCTs) intra-arterial treatment (IAT) has been proven effective and safe for patients with acute ischemic stroke (AIS). So far, there seemed to be no interaction between older age (>80) and main treatment effect. We studied the association of older age with outcome and adverse events after IAT in a cohort of intra arterially treated patients. Methods and findings Data from all AIS patients with proven proximal anterior circulation cerebral artery occlusion who were intra arterially treated between 2002 until the start of the MR CLEAN trial were studied retrospectively. Duration of the procedure, recanalization (Thrombolysis In Cerebral Infarction score (TICI)), early neurological recovery (i.e. decrease on NIHSS of ≥ 8 points) after one week or at discharge, good functional outcome at discharge by modified Rankin Scale (mRS ≤ 2) and the occurrence of neurological and non-neurological adverse events were assessed and the association with age was investigated. In total 315 patients met our inclusion criteria. Median age was 63 years (range 22–93) and 17 patients (5.4 %) were over 80. Age was inversely associated with good functional outcome (adjusted Odds Ratio (aOR) 0.80, 95 % CI: 0.66–0.98) for every 10 years increase of age. Age was not associated with longer duration of the procedure, lower recanalization rate or less early neurological recovery. The risk of all adverse events (aOR 1.27; 95 % CI: 1.08–1.50) and non-neurological adverse events (aOR 1.34; 95 % CI: 1.11–1.61) increased, but that of peri-procedural adverse events (aOR 0.79; 95 % CI: 0.66–0.94) decreased with age. Conclusion Higher age is inversely associated with good functional outcome after IAT in patients with AIS. However, treatment related adverse events are not related to age. These findings may help decision making when considering treatment of older patients with AIS.